Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2024
DOI: 10.2147/jhc.s450423
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism as a Potential Target of Liver Cancer

Kangze Wu,
Feizhuan Lin

Abstract: Hepatocellular carcinoma (HCC) stands as a severe malignant tumor with a profound impact on overall health, often accompanied by an unfavorable prognosis. Despite some advancements in the diagnosis and treatment of this disease, improving the prognosis of HCC remains a formidable challenge. It is noteworthy that lipid metabolism plays a pivotal role in the onset, development, and progression of tumor cells. Existing research indicates the potential application of targeting lipid metabolism in the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 182 publications
0
0
0
Order By: Relevance
“… 83 , 88 Immunohistochemistry (IHC) testing shows increased GDF15 expression in moderate to severe HCC, correlating with pathological grading, but not with age, gender, or tumor node metastasis (TNM) stage. 29 , 89 The Barcelona Clinic Liver Cancer (BCLC) system, the most reliable staging method for HCC, includes five stages: stage 0 (extremely early), stage A (early), stage B (intermediate), stage C (advanced), and stage D (end-stage). 84 , 90 A study by Chen et al found elevated GDF15 levels in patients with BCLC-B and BCLC-C compared to healthy individuals and those with BCLC-A.…”
Section: Gdf15 As a Target For Hcc Diagnosis Prognosis And Treatmentmentioning
confidence: 99%
“… 83 , 88 Immunohistochemistry (IHC) testing shows increased GDF15 expression in moderate to severe HCC, correlating with pathological grading, but not with age, gender, or tumor node metastasis (TNM) stage. 29 , 89 The Barcelona Clinic Liver Cancer (BCLC) system, the most reliable staging method for HCC, includes five stages: stage 0 (extremely early), stage A (early), stage B (intermediate), stage C (advanced), and stage D (end-stage). 84 , 90 A study by Chen et al found elevated GDF15 levels in patients with BCLC-B and BCLC-C compared to healthy individuals and those with BCLC-A.…”
Section: Gdf15 As a Target For Hcc Diagnosis Prognosis And Treatmentmentioning
confidence: 99%